2016
DOI: 10.1088/0957-4484/27/42/425207
|View full text |Cite
|
Sign up to set email alerts
|

A porous Si-emitter crystalline-Si solar cell with 18.97% efficiency

Abstract: A p-n junction was made on p-type Si〈100〉 wafer (15 × 15 × 0.2 mm(3) in size) via phosphorous diffusion at 900 °C. Porous Si (PSi) with ultralow reflectivity (<0.3% in the ultraviolet and visible regimes) was achieved by etching a Ag-coated n(+) Si emitter in a solution of HF, H2O2 and H2O. The PSi was found to mainly consist of Si nanocrystallites with bandgap widths larger than that of bulk Si. Compared to other micro- or nanostructured Si-based crystalline-Si solar cells found in the literature, this PSi on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The PL emission from b-Si is another indication that Si nanocrystals exist as shown in Fig. 2c [ 10 , 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PL emission from b-Si is another indication that Si nanocrystals exist as shown in Fig. 2c [ 10 , 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This type of Si, or black Si (b-Si), has attracted much attention for its potential application in broadband response photovoltaics [ 7 9 ]. To date, investigations of b-Si solar cell have focused on such a configuration that the b-Si layer is at the front of the solar cell [ 10 19 ]. In this case, electron-hole pairs induced by the sub-band gap near infrared (NIR) absorption at the b-Si layer are far away from the PN junction zone and cannot be decomposed by the built-in field to become charge carriers, making the sub-band gap NIR photovoltaic response impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By selecting the material based on the band gap energy by considering the atomic lattice matching, nanostructured silicon material could be a promising candidate for the top layer of the tandem structure. For decades, there has been extensive research into potential candidates for the top layer, and the most prominent Sibased materials are Si nanowire [4] and nanopore arrays [5,6]. These structures are composed of an array of vertically aligned Si nanostructures, which can not only reduce the volume of semiconductor absorber but can provide nearly ideal photon absorption across the solar spectrum for high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon-based optoelectronic devices and their monolithic integration for future photonic integrated circuits (PICs) require CMOS compatibility in terms of their fabrication and operation. A large number of photonic devices based on silicon-like modulators and photodetectors have already been reported in the literature, but achieving a Si-based optical source is still a major challenge. The main bottleneck on this context is the inherent indirect band gap nature of bulk Si, exhibiting poor near-infrared (NIR) emission. , Over the last several years, new pathways have been explored to develop Si-based light emitters using various Si nanostructures such as nanowires, quantum dots, , and Group IV alloys. , One-dimensional (1D) Si nanostructure arrays such as nanowires are preferred for these kinds of applications because of their ability to form versatile templates, which assist in fabrication of radial heterojunctions. , In particular, vertically oriented cone-like nanostructures termed as black silicon, attractive due to its excellent antireflection feature, are promising for Si-based photovoltaic technology. ,, The conical black-Si (bSi) nanostructures containing Si nanocrystallites on the surface not only exhibit an excellent light trapping behavior but also have the capability of providing intense light emission and enhanced light extraction. , It has already been demonstrated that texturing or patterning the surface of GaN- and InGaN-based LEDs enhances the light extraction efficiency by reducing the total internal and Fresnel’s reflections suffered by the emitted light rays. Therefore, a conical p-n heterojunction between cone-like bSi nanostructures with an appropriate direct and wide band gap semiconductor appears potentially attractive for efficient Si-based light-emitting devices.…”
Section: Introductionmentioning
confidence: 99%